Leadership, Facilities, and Psychological Mechanisms in Teacher Performance: The Mediating Effects of Teaching Enthusiasm and Job Satisfaction - Setiawan, Apep; Basrowi; Khaeruman; Hisniati, Sally Badriya (Journal Corner of Education, Linguistics, and Literature, 2025)
Teacher performance is a critical determinant of educational quality, particularly in vocational high schools where learning outcomes are closely linked to workforce readiness. This study examines the effects of paternalistic leadership and school facilities on teacher performance by incorporating teaching enthusiasm and job satisfaction as mediating variables. Using a quantitative explanatory design, data were collected from teachers in public vocational high schools in Cilegon City, Indonesia. Structural Equation Modeling (SEM) was employed to analyze both direct and indirect relationships among the study variables. The results reveal that paternalistic leadership and school facilities have significant positive effects on teaching enthusiasm and job satisfaction. Furthermore, both teaching enthusiasm and job satisfaction significantly enhance teacher performance. Mediation analysis confirms that teaching enthusiasm and job satisfaction partially and sequentially mediate the relationships between paternalistic leadership, school facilities, and teacher performance. These findings underscore the importance of integrating leadership practices, adequate infrastructure, and psychological factors to improve teacher performance. This study contributes to the educational management literature by proposing a dual-mediation SEM model that explains how organizational factors translate into performance outcomes in vocational education settings.